Evaluation on Bioactive Secondary Metabolites from Fingerroot (Boesenbergia rotunda) as a Potent α-Glucosidase Inhibitor: In silico Study: In silico Study - Firdaus, Yazdaniar Fajri Halimi; Hariyanto, Nova Alfian; Kurnia, Irmayanti Tri; Lestari, Dinda Ayu; Suwandari, Suhartini; Haq, Kautsar Ul; Phuwapraisirisan, Preecha; Ramadhan, Rico (Journal of Bio-Molecule Research and Engineering, 2023)
Fingerroot (Boesenbergia rotunda) is a medicinal plant that has been reported to have anti-diabetic properties. However, the mechanism of action and the active compounds responsible for this effect are not well understood. In this study, we performed molecular docking study of isolated compound from fingerroot against N-terminal-human intestinal maltase-glucoamylase, one class of α-glucosidase. Inhibiting enzymatic activity of alpha glucosidase could potentially control sugar levels. In addition to panduratin A showing moderate inhibition activity against N-terminal-human intestinal maltase-glucoamylase.